Kualitas Elemen Fisik Ruang Publik pada Koridor Komersial Pasar Sudimampir Kota Banjarmasin - Annisa; Muhammad Yusuf Ridhani (Archvisual: Jurnal Arsitektur dan Perencanaan, 2024)
The Sudimampir Market area is a public space located along the Sudimampir and Ujung Murung Road corridors and along the banks of the Martapura River, which is used to carry out various activities, especially commercial activities in Banjarmasin. The Sudimampir Market area is part of the old city area where some of the elements that form the physical area are not feasible or visible. This research aims to examine the implementation of 8 physical elements of public space along the commercial corridor of the Sudimampir Market area using Hamid Shirvani's (1985) theory. The research method used in this research is a descriptive qualitative method, which is then analysed, and conclusions are obtained, starting with direct observation in the field, obtaining data which is then identified as the physical elements of forming urban space around the Sudimampir Market area. The results obtained show that the Sudimampir Market area of Banjarmasin City has not fulfilled the criteria for applying the physical elements of forming urban space, land use and building functions have a fairly good quality, but for circulation and parking, pedestrian ways, open space, activity support, signage and preservation still need to improve quality with better planning and design in the future.